Validation of a scale to evaluate the abusive use of technologies (Computer, cell phone, tablet, among others) - King,Anna Lucia Spear (2019)
BACKGROUND INFORMATION: Daily, prolonged interactivity of individuals with technologies (computer, cell phone, tablet, among others) impacts life and significantly changes habits, behaviors, personal and social relationships. Technologies lead to a multitude of advantages, but attention is required concerning possible damages. OBJECTIVE: Validation of a scale to evaluate the abuse use of technologies (TAUS). METHOD: TAUS validation was carried out in 5 phases: (1) initial scale construction with 20 questions, (2) expert evaluation, (3) application to 200 volunteers, (4) statistical analysis and results, (5) preparation of the final version of the validated TAUS. We used the R statistical program and the “dplyr” package version 3.4.2 to present descriptive statistics, to test hypotheses of means differences and for factorial analysis. Factor analysis was used for the orthogonal model. The method used was Principal Components based on Spearman’s correlation matrix. RESULTS: The results provided a final, validated version of a TAUS suitable for clinical and research contexts. The last step of the study was to calculate Cronbach’s alpha, in order to measure the internal consistency of the scale. The value found was 0.910, which is considered good. CONCLUSIONS: This Technology Abuse Scale may contribute to future studies, to the conscious use of technologies, to a reduction of physical and emotional damage and to an improvement of the subjects’ quality of life.